(untitled) (Teología, 2015)
In his exposition, Carlos Galli dialogues with the valuable presentation of Cardinal Walter Kasper, summarizing the reception of the conciliar ecclesiology in Argentina. This dialogue is centered on four points, the dialectic of liberation – freedom in the dialogue of the Church with Modernity, the argentine reception of her ecclesiology, considering the relations between the faith of the People of God and the cultures of the Peoples, the radical evangelical reform in the light of the paradigm of the missionary conversion of all the People of God and of all in the People of God. The genre of the text puts together the interpretative commentary and the more constructive than critical theological dialogue.